2011
DOI: 10.1007/s10735-011-9317-7
|View full text |Cite
|
Sign up to set email alerts
|

Suppressor of cytokine signalling protein SOCS3 expression is increased at sites of acute and chronic inflammation

Abstract: Treatment of cells with cytokines and growth factors leads to the synthesis of Suppressor of Cytokine Signalling (SOCS) proteins that act as potent negative regulators of signalling via the Jak/STAT pathway. We used immunohistochemistry to identify cells and pathologies where SOCS3 expression might influence acute and chronic inflammatory responses in human tissues. Epitope and GFP tagged SOCS3 fusion proteins were localised predominantly in the nucleus of transfected cells and a validated anti SOCS3 antiserum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

8
46
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(54 citation statements)
references
References 37 publications
8
46
0
Order By: Relevance
“…It has previously been reported that SOCS3 expression is increased during both acute and chronic inflammation [41]. Gordon et al reported that SOCS3 siRNA-mediated gene silencing in M1-activated human monocyte-derived macrophages decreased the expression of proinflammatory factors [42].…”
Section: Discussionmentioning
confidence: 98%
“…It has previously been reported that SOCS3 expression is increased during both acute and chronic inflammation [41]. Gordon et al reported that SOCS3 siRNA-mediated gene silencing in M1-activated human monocyte-derived macrophages decreased the expression of proinflammatory factors [42].…”
Section: Discussionmentioning
confidence: 98%
“…SOCS-3 expression is increased, however, at sites of acute and chronic inflammation (White et al, 2011), and IL-6 has been reported to promote acute and chronic inflammatory disease in the absence of SOCS-3 (Croker et al, 2012). Moreover, conditional deletion of the SOCS-3 gene in hematopoietic and endothelial cells of transgenic mice results in death caused by severe inflammatory lesions in the peritoneal and pleural cavities (Croker et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…SOCS proteins regulate development, homeostasis and disease pathogenesis [34]. Indeed, SOCS expression is found increased in inflamed human tissues [37], making them potential markers of ongoing inflammation. Furthermore, loss-and gain-of-function studies evidenced the important role of SOCS proteins in regulating the course of inflammation in different experimental models [6,21,27,35], including cardiovascular diseases [32].…”
mentioning
confidence: 99%